FUNCTIONS OF HERO AND FICTION IN THE ARTISTIC INTERPRETATION OF HISTORICAL ACTUALITY - RAXMATOVA NILUFAR MAQSUD QIZI (Лучшие интеллектуальные исследования, 2024)
The glorious history of the peoples of Central Asia has given rise to many legends about the heroism of its legendary heroes, such as Shirak, Tomaris, Spitamen, Jaloliddin Manguberdi. Historical writers, transforming the heroism of historical figures and the illustrious history of Turkic-speaking peoples, made an invaluable contribution to the development of historical prose not only in Uzbek, but also world literature. Among these writers, the work of the Uzbek writer Mirkarim Asim occupies a special place. The writer devoted his entire life to creating historical stories, raised new generations in the spirit of love for the historical past and famous people of the East, and glorified the ideas of patriotism and humanism.